BSU SPECIALIST AT THE DEPARTMENT OF PSYCHOLOGY FOR THE QUESTION OF THE RELATIONSHIP BETWEEN PROFESSIONAL BURNOUT AND COGNITIVE REGULATION OF EMOTIONS (Conferencea, 2024)
According to a widespread explanation, professional burning is a chronic, negative, service -related mood in individuals, characterized by depletion, accompanied by stress, a reduced sense of efficiency, reduced motivation, and the development of dysfunctional attitudes and behavior. Consequently, it is important for a person to be able to regulate their emotions.The regulation of emotions implies the combination of all processes involved in monitoring, evaluating and transforming the emotional reaction. Cognitive Regulation of Emotion - This is the answer to emotionogenic stimuls that allows a person to control his or her emotional state.